The Role of Gum Arabic for a Protective Kidney Dysfunction Induced Gentamicin on Diabetes Rats - Garsa Ali Alshehry (Advances in Materials Science and Engineering)
The target of this study was to estimate Gum Arabic for total phenols and flavonoids. In addition to antioxidant activities, estimate gum Arabic for total phenols and flavonoids. In addition to antioxidant activities, the problem of studying the potential effect of experimental diabetes kidney failure induced by gentamicin and the effect of taking gum Arabic. The results were observed to increase the content of phenols and total flavonoids. The method of study was that diabetic rats groups were fed on a basal diet, and intake of drinking water separately at concentrations of 5, 10, 15, and 20 g gum Arabic dissolved in 100 ml of water/day indicated that the lipid profile gradually decreased in triglycerides from group (1) was 128.30 mg/dL to group (4) was 77.53, total cholesterol-lowering from 163.18 mg/dL to 111.19 mg/dL, LDL reducing from 101.61 mg/dL to 37.83 mg/dL, VLDL lessening from 25.73 mg/dL to 15.51 mg/dL, and glucose reduced from 192.52 mg/dL to 111.24 mg/dL. and glucose became less from 192.52 mg/dL to 111.24 mg/dL. The kidney functions indicated to creatinine, urea, uric acid, blood urea nitrogen, and bilirubin were decreased from 1.34, 0.95, 2.24, 45.61, and 0.66 mg/dl in group (1) to 0.78, 29.84, 2.12, 16.25, and 018 mg/dL in group (4), respectively, when taking Gum Arabic. Furthermore, in the treatment group with Gum Arabic at different doses, the results could be noticed that sodium and calcium were gradually increased, and there was gradual reduction in potassium, phosphor, and magnesium. The results found that the treatment with GA had lowered the effects of gentamicin and streptozotocin, as evidenced by improvement of the lipids profile, kidney function, some minerals in serum, and antioxidant enzyme in kidney tissue, which may be referred to as its content of antioxidant active ingredients. Therefore, it is recommended that Gum Arabic is a beneficial dietary tool in reducing the advancement of chronic kidney disease in diabetic rats.